A review of microbes and chemical contaminants in dairy products in sub‐Saharan Africa. Issue 2 (27th January 2021) - Akinyemi, Muiz O.; Ayeni, Kolawole I.; Ogunremi, Omotade R.; Adeleke, Rasheed A.; Oguntoyinbo, Folarin A.; Warth, Benedikt; Ezekiel, Chibundu N.
Abstract: Animal milk types in sub‐Saharan Africa (SSA) are processed into varieties of products using different traditional methods and are widely consumed by households to support nutritional intake and diet. Dairy products contain several microorganisms, their metabolites, and other chemical compounds, some with health benefits and many others considered as potential health hazards. Consumption of contaminated milk products could have serious health implications for consumers. To access the safety of milk products across SSA, studies in the region investigating the occurrences of pathogens as well as chemical compounds such as heat stable toxins and veterinary drug residues in animal milk and its products were reviewed. This is done with a holistic view in light of the emerging exposome paradigm for improving food safety and consumer health in the region. Herein, we showed that several published studies in SSA applied conventional and/or less sensitive methods in detecting microbial species and chemical contaminants. This has serious implications in food safety because the correct identity of a microbial species and accurate screening for chemical contaminants is crucial for predicting the potential human health effects that undermine the benefits from consumption of these foods. Furthermore, we highlighted gaps in determining the extent of viral and parasitic contamination of milk products across SSA as well as investigating multiple classes of chemical contaminants. Consequently, robust studies should be conducted in this regard. Also, efforts such as development cooperation projects should be initiated by all stakeholders including scientists, regulatory agencies, and policy makers to improve the dairy product chain in SSA in view of safeguarding consumer health.